The perception of self-directed learning abilities among the pre-clinical undergraduate medical students of Faculty of Medicine, Universiti Teknologi MARA /Nurul Alimah Abdul Nasir. - Nurul Alimah , Abdul Nasir (2022)
Self-directed learning (SDL), a key component of life-long learning, is crucial among healthcare professionals. The ever-evolving knowledge on medicine will require healthcare professionals to always update themselves on the latest information in ensuring the betterment of patients. Therefore, SDL skills needs to be developed in medical students since their undergraduate years. The aim of this study was to assess the SDL perceived abilities and determine factors that promote or deter the SDL among preclinical medical students in Universiti Teknologi MARA (UiTM). A mixed model design was used in this study. A validated 20-item SDL Instrument (SDLI) questionnaire was used to determine the level of students’ SDL abilities quantitatively. Then, students were asked to answer open-ended questions on what they perceived as the promoting or deterring factors on implementing SDL. From this study, high SDLI scores were observed among these students which suggested them to have good SDL abilities. Guide and support from the lecturers and faculty are important influencing factors among these students, both in promoting and deterring the implementation of SDL. These factors also influence the level of motivation for the students to learn. Distractions from current technology and social media play a big role as a deterring factor of SDL. Teaching innovations that incorporate social media and technology may promote SDL. Overall findings from this study should influence lecturers and faculty to design appropriate teaching-learning activities that will guide and support SDL among the students.